Acute Unilateral Myopia Induced by Add-On Aripiprazole: A Case Report. Issue 1 (1st March 2016) - Gunes, Mehmet; Demir, Suleyman; Bulut, Mahmut; Kaya, Mehmet Cemal; Atli, Abdullah; Ibiloglu, Aslihan Okan; Yuksel, Harun
ABSTRACT: The partial agonist aripiprazole is a novel atypical antipsychotic with a relatively safer side effect profile. Acute unilateral myopia is a very rare condition that is commonly associated with drug use. Here, we present a woman diagnosed with obsessive-compulsive disorder (OCD) and major depressive disorder (MDD) who have been treated for two years in our clinic. She was on fluoxetine (Prozac) 80 mg/day when adding aripiprazole (Abilify) 10 mg/day as an augmentation agent has triggered unilateral myopia. After cessation of aripirazole her myopia has disappeared. Psychiatrists should keep in mind that unilateral myopia as a side effect may develop after combining aripiprazole with fluoxetine in patients with OCD and MDD.